Reconstruction of a Scrotum by Combining Two Skin Flaps in a Ball Shape - Kazuya Kashiyama; Motoi Nakano; Akihito Higashi; Shoko Ashizuka; Yuki Moriuchi; Atsuhiko Iwao; Katsumi Tanaka (Case Reports in Urology)
Background. The scrotum functions to maintain spermatogenesis and hormonal production of Leydig cells by preventing the testicles from rising in temperature and protecting them from the outside world. The scrotum, along with the penis, is also an organ that symbolizes masculinity. Therefore, deformity or loss of the scrotum can be a major psychological problem. Various scrotal reconstruction techniques have been reported. In these papers, there is some discussion about the type of skin flap, but little discussion about the method of suturing the skin flap. We devised a way to reconstruct a scrotum to a natural size by suturing two skin flaps together to form a ball shape. Case Presentation. Case 1 was a patient with a missing scrotum due to Fournier’s gangrene. Total resection of the scrotum, including the bilateral testes, was performed to save his life. Reconstructive surgery was performed 11 days after the initial surgery. Reconstruction was performed using bilateral gluteal fold flaps. Case 2 was a patient with a congenital defect of the scrotum. The testis on the right side exhibited cryptorchidism, and the scrotum was missing, and the testis on the left side was encased in a hypoplastic scrotum. Reconstruction was performed using an internal pudendal artery perforator flap. Conclusion. There are two types of scrotal defects: those with testes present and those with testes missing. This method can be used for both types of scrotal defects, and we were able to create a scrotum that satisfied each patient.